Prophylactic and Therapeutic Effects of Interleukin-2 (IL-2)/Anti-IL-2 Complexes in Systemic Lupus Erythematosus-Like Chronic Graft-Versus-Host Disease - Heiler, Stefan; Lötscher, Jonas; Kreuzaler, Matthias; Rolink, Johanna; Rolink, Antonius (Frontiers in Immunology, 2018)
Abstract Murine chronic Graft-versus-Host-Disease (cGvHD) induced by injection of parental lymphocytes into F1 hybrids results in a disease similar to Systemic Lupus Erythematosus. Here we have used DBA/2 T cell injection into (C57BL/6xDBA/2)F1 (BDF1) mice as a model system to test the prophylactic and therapeutic effects of IL-2/anti-IL-2 immune complexes on the course of cGvHD. Our findings demonstrate that pretreatment with Treg inducing JES6/IL-2 complexes render BDF1 mice largely resistant to induction of cGvHD whereas pretreatment with CD8+ T cell/NK cell inducing S4B6/IL-2 complexes results in a more severe cGvHD. In contrast, treatment with JES6/IL-2 complexes four weeks after induction had no beneficial effect on disease symptoms. However, similar treatment with S4B6/IL-2 complexes led to a significant amelioration of the disease. This therapeutic effect seems to be mediated by donor CD8+ T cells. The fact that a much stronger cGvHD is induced in BDF1 mice depleted of donor CD8+ T cells strongly supports this conclusion. The contrasting effects of the two different IL-2 complexes are likely due to different mechanisms.